Biotransformation of rambutan (Nephelium lappaceum L.) seed into a cocoa powder-like product - Chai, Kong Fei (2017)
Rambutan (Nephelium lappaceum L.) is an exotic fruit originally found in Southeast Asia. There is a glut of rambutan every year which leads to wastage. A novel way to reduce wastage is to convert rambutan seeds into a cocoa powder-like product. Thus, the objectives of this study were to select the best rambutan variety for fermentation by comparing the physicochemical properties of pulp and seed of eleven varieties of rambutan fruit with those of cocoa pulp and seed, to determine the physicochemical properties of rambutan fruit sweatings, seed and seed fat during solid state fermentation at different fermentation times and turning intervals, to optimize the roasting process of rambutan seed from fermented and dried rambutan fruit and determine the physicochemical properties of rambutan seed powder, and to determine the toxicology safety of the roasted rambutan seed powder using brine shrimp lethality assay. Eleven varieties of rambutan were examined in this study, and most of the physicochemical properties of a wild type rambutan, WT1, were found to be similar to those of cocoa bean. However, due to subsequent unavailability of the variety, rambutan Clone R4 was chosen to be the best variety to be investigated on the effect of fermentation as its titratable acidity was not significantly different from that of cocoa bean and the total sugar content of the pulp is comparable to that of cocoa pulp. Besides, the seed had the highest crude fat content (39.13 %) and lowest saponin content (14.27 mg soya saponin/100 g). Peeled rambutan fruit Clone R4 was subjected to natural fermentation in covered perforated plastic boxes for 0, 1, 3, 5, 7 and 10 days at room temperature. Fermentation time significantly affected the physicochemical properties of sweatings (liquid released naturally from the fruit), seed and seed fat. The study showed that 8 days of fermentation was regarded as sufficient to produce well fermented seeds. The effect of turning intervals during fermentation for 8 days did not lead to significant changes in the properties of sweatings. Also, there was no significant difference on most of the physicochemical properties of the fermented seeds, between 24 and 48 hours of turning intervals. Considering practical aspects of fermentation in both small and large scale contexts, turning at 48 hours intervals for eight days is recommended. Fermentation for 8 days is also recommended as it served to eliminate microorganisms that are potentially harmful. Roasting conditions (time and temperature) of seeds after fermentation for 8 days with a 48-hour turning interval significantly affected the physicochemical properties of the fermented seeds. GCMS analysis showed that roasted seed powder contained pyrazines, indicating that the powder has aroma and flavor similar to that of cocoa powder. Results from the brine shrimp lethality assay showed that the LC50 of roasted rambutan seed powder extract was 7.07×104 μg/mL and is considered as non-toxic. The overall findings of the study indicate that it is possible to obtain a cocoa powder-like product from the seeds of rambutan that had undergone fermentation that is relatively safe for consumption.